Visible to NIR absorbing C–N and C–C bonding squaraines: A computational study. (29th August 2017) - Tripathi, Anuj; Dhanda, Promila; Prabhakar, Chetti
Abstract: We report a comparative computational study of 2 series of molecules with C–N bonding squaraines (NSQ) and C–C bonding squaraines (CSQ), having absorption from visible to near infrared region (350‐800 nm). The NSQ are considered as molecules with break‐in conjugation, and CSQ are considered as molecules with complete conjugation in molecular backbone. The lowest electronic excitations in CSQ molecules are always having around 200 nm red shifted absorption than its corresponding NSQ molecules. The reason for this drastic red shift in CSQ series than NSQ has been systematically studied by density functional theory, time‐dependent density functional theory, and symmetry adopted cluster configuration interaction methods. The CSQ series are showing less charge transfer than NSQ, but having small diradical character. This study may be helpful in design and synthesis of new squaraine dyes, which are useful in materials applications. Abstract : Linear optical properties of 2 series of squaraine molecules (NSQ & CSQ) have been studied by DFT, TDDFT, and SAC‐CI methods. Both the series (NSQ & CSQ) are considered as donor‐acceptor‐donor–type of molecules, but NSQ series are showing larger charge transfer than CSQ series. The larger red shift of the CSQ when compared with its corresponding NSQ is due to the extended pi backbone along with presence of some diradicaloid character. These molecules are transparent in visible to NIR region, which is suitable for application in the region of interest.